2007
DOI: 10.1128/jvi.01782-06
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus Open Reading Frame (ORF) 3b, ORF 6, and Nucleocapsid Proteins Function as Interferon Antagonists

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV) is highly pathogenic in humans, with a death rate near 10%. This high pathogenicity suggests that SARS-CoV has developed mechanisms to overcome the host innate immune response. It has now been determined that SARS-CoV open reading frame (ORF) 3b, ORF 6, and N proteins antagonize interferon, a key component of the innate immune response. All three proteins inhibit the expression of beta interferon (IFN-␤), and further examination revealed that these S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
714
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 639 publications
(756 citation statements)
references
References 33 publications
21
714
0
2
Order By: Relevance
“…The 3b, ORF6 and nucleocapsid proteins of SARS-CoV function as interferon antagonists by inhibiting the expression of beta interferon (Kopecky-Bromberg et al, 2007). Of these, the ORF6 protein inhibits nuclear translocation of STAT1, a transcription factor that is required for the activation of interferon-responsive promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The 3b, ORF6 and nucleocapsid proteins of SARS-CoV function as interferon antagonists by inhibiting the expression of beta interferon (Kopecky-Bromberg et al, 2007). Of these, the ORF6 protein inhibits nuclear translocation of STAT1, a transcription factor that is required for the activation of interferon-responsive promoters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that many viral IFN antagonists interfere with the IRF-3 and/or NF-kB signalling pathways (Basler et al, 2003;Boxer et al, 2009;Kochs et al, 2007;Kopecky-Bromberg et al, 2007). We next determined the impact of Nsp2 expression on the IRF-3-or NF-kBdependent, SeV-induced activation of the IFN-b promoter.…”
Section: Nsp2 Inhibits the Activation Of Irf-3-and Nf-kbresponsive Prmentioning
confidence: 99%
“…Others can induce proteasomedependent degradation of IRF-3. For example, Ebola virus VP35 protein and severe acute respiratory syndrome coronavirus (SARS-CoV) ORF3b, ORF6, N and papain-like protease (PLP) proteins inhibit IRF-3 activation (Basler et al, 2003; Clementz et al, 2010;Devaraj et al, 2007;Frieman et al, 2009;Kopecky-Bromberg et al, 2007). Classical swine fever virus N pro and rotavirus NSP1 induce IRF-3 degradation (Bauhofer et al, 2007;Graff et al, 2007).…”
Section: The Pl2 Protease Domain Of Nsp2 Inhibits Ifn-b Inductionmentioning
confidence: 99%
See 2 more Smart Citations